KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DI RSUD MOROWALI KECAMATAN BUNGKU TENGAH - Adriansyah, Adriansyah (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
This study aims to determine and analyze the influence of service quality consisting of Physical Evidence, Empathy, Reliability, Responsiveness and Guarantee to patient satisfaction In Morowali District Hospital Central Bungku. The problem in this research is whether the service quality consisting of Physical Evidence, Empathy, Reliability, Responsiveness and Guaranteed simultaneously and partially have a significant effect on patient satisfaction In Morowali District Hospital of central Bungku. Based on that opinion, the sample size is 15 (5 1) 15 (6) 90. To prove the hypothesis, the research use multiple regression analysis. From the results of the study found that simultaneously the quality of service significantly influence patient satisfaction In Morowali District Hospital Central Bungku. This means that the variables of Physical Evidence, Empathy, reliability, partially significant effect on patient satisfaction variable, name Response Power and Assurance partially have no significant effect on patient satisfaction.